Desenvolvimento de programa aplicativo de apoio à configuração da função direcional de sobrecorrente em relés de proteção digitais - Silva, Elvio da (2019)
The configuration tools and procedures for a given protection function are different for each protection relay manufacturer available and sometimes even different for a particular manufacturer. This lack of uniformity causes difficulties in understanding the operation of the desired protection function and how to set them . In this way, the objective of this study was to develop a computational tool that support the configuration of the directional overcurrent protection function. For this, the behavor of three relay of different manufacturers were analyzed and the main variables involved were identified. The tool was developed based on Python language, using the quadrupole theory applied to the solution of missing three-phase systems. The tool can contemplate cases of short circuit without load current, with load current or even unbalanced systems. The application simulates faults along a transmission line that interconnects two equivalent sources of Thêvenin and also reverse faults to the relays at its ends. After applying the faults, the program generates a series of graphs, relating the variables of interest of each relay to the length of the line. The reverse fault of each relay is also shown on the same graph, giving an overall idea of all faults. From the observation of the behavior of the fault, through the generated graphs, the user can define the adjustment of the directional function of the overcurrent. The software does not propose adjustments to the function, but it helps the user to understand the pattern of each variable of interest of the relay for the faults, providing a graphical vision of what the adjustment could be. The results presented in this paper are limited to the study of directional overcurrent function for a phase-to-ground fault on a transmission line. However, with the concepts presented here, it is possible expand to other types of problems and increase the size of the system. It can be concluded that the tool presented here could help improve the understanding of directional overcurrent function both within the classroom and for protection professionals in the electricity sector.